2023
DOI: 10.1038/s41467-023-36646-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic promotions between CO2 capture and in-situ conversion on Ni-CaO composite catalyst

Abstract: The integrated CO2 capture and conversion (iCCC) technology has been booming as a promising cost-effective approach for Carbon Neutrality. However, the lack of the long-sought molecular consensus about the synergistic effect between the adsorption and in-situ catalytic reaction hinders its development. Herein, we illustrate the synergistic promotions between CO2 capture and in-situ conversion through constructing the consecutive high-temperature Calcium-looping and dry reforming of methane processes. With syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…22,23 Significant scientific interest has been focused around the interactions between components because of the outstanding effects that they offer beyond the sum of the individual components. [24][25][26] For instance, composite electrocatalysts with conductive substrates possess optimized charge-transport/ mass-transfer properties. 27,28 Composite photocatalysts have exhibited appropriate energy levels with a multifold increase in performance.…”
Section: Xiaotian Wumentioning
confidence: 99%
“…22,23 Significant scientific interest has been focused around the interactions between components because of the outstanding effects that they offer beyond the sum of the individual components. [24][25][26] For instance, composite electrocatalysts with conductive substrates possess optimized charge-transport/ mass-transfer properties. 27,28 Composite photocatalysts have exhibited appropriate energy levels with a multifold increase in performance.…”
Section: Xiaotian Wumentioning
confidence: 99%
“…They found that the structural stability and cycling performance of the CaO sorbent was improved, which was again a manifestation of the synergistic effect. Shao et al 16 attributed the synergistic effect to the facilitation of the transfer of substances because of the proximity of the adsorption and catalytic sites. The studies mentioned above indicate that the synergistic effect between the catalyst and adsorbent can significantly improve the performance of DFMs and seems to be closely related to mass transfer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The adsorptive/catalytic interface, CO 2 capacity, and CO 2 conversion of the DFMs were found to be strongly dependent on the Ni loading density and Ni particle size effect. 30 To date, the effect of Ni loading density on the structure and ICCU performance of Ni-CaO DFMs for CaL-RWGS remains unknown, and it merits further investigation. An in-depth understanding of the Ni loading effect will certainly provide significant guidance for the rational design of robust DFMs for integrated CO 2 capture and CO production.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Shao et al developed Ni-CaO- x composite DFMs with varying Ni loadings for CaL@DRM. The adsorptive/catalytic interface, CO 2 capacity, and CO 2 conversion of the DFMs were found to be strongly dependent on the Ni loading density and Ni particle size effect . To date, the effect of Ni loading density on the structure and ICCU performance of Ni-CaO DFMs for CaL-RWGS remains unknown, and it merits further investigation.…”
Section: Introductionmentioning
confidence: 99%